1976
DOI: 10.1111/j.1365-2125.1976.tb00356.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered Distribution of Digoxin in Renal Failure—a Cause of Digoxin Toxicity?

Abstract: 1Three cases are described in which renal failure was accompanied by a lowered apparent volume of distribution of digoxin. In two cases this resulted in frank digoxin toxicity and in one equivocal toxicity. In all three cases digoxin plasma levels were greater than 2 ng/ml. 2 The possible causes of the abnormal distribution of digoxin in renal failure are discussed. 3 Recommendations are outlined for the use of digoxin in patients with renal failure aimed at circumventing the problem raised by a lowered appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1
1

Year Published

1978
1978
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 19 publications
0
34
1
1
Order By: Relevance
“…Finally, the selection of patients in our study may be different from that in the cited studies of the apparent volume of distribution of digoxin in patients with renal failure (Reuning et al, 1973;Szefler & Jusko, 1973;Aronson & Grahame-Smith, 1976). Despite the fact that the glomerular filtration rates were of the same magnitude, the serum electrolyte balance was probably less disturbed in our patients.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…Finally, the selection of patients in our study may be different from that in the cited studies of the apparent volume of distribution of digoxin in patients with renal failure (Reuning et al, 1973;Szefler & Jusko, 1973;Aronson & Grahame-Smith, 1976). Despite the fact that the glomerular filtration rates were of the same magnitude, the serum electrolyte balance was probably less disturbed in our patients.…”
Section: Discussioncontrasting
confidence: 43%
“…Thus, in our study the serum potassium range was 3.9-4.6 mmol'l, whereas the potassium concentrations in the previous studies, when indicated, were usually higher. Since hyperkalaemia has been suggested as a possible cause of reduced tissue binding of digoxin in renal failure (Aronson & Grahame-Smith, 1976), this difference in serum electrolytes may be of importance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 The available literature suggests that the loading dose of digoxin should be reduced for patients with renal dysfunction, because of a decreased volume of distribution for this drug in these patients. [4][5][6][7][8] However, the recommendations are inconsistent with respect to the extent of dose reduction, as well as the degree of renal dysfunction that necessitates a reduction. The product monograph recommends decreasing the loading dose from 8-12 µg/kg to 6-10 µg/kg for patients with renal insufficiency but does not define insufficiency.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported three cases of patients with renal failure and lowered apparent Vd who became toxic (two definitely and one equivocally so) after usual or even low loading doses of digoxin (Aronson & Grahame-Smith, 1976b). I have since observed another patient who developed equivocal toxicity in similar circumstances.…”
Section: Usefulness Of the Published Nomograms And Equationsmentioning
confidence: 84%